Composition, Abundance and Distribution of Chaetognaths Along the Pacific Coast and Adjacent Internal Waters of the Philippines - Noblezada, Mary Mar; Campos, Wilfredo (Science Diliman: A Journal of Pure and Applied Sciences; Vol 19 No 1 (2007), 2007)
Chaetognath species composition, distribution and relative abundance along the Pacific Coast and the internal waters of the Philippines are presented based on the analysis of 12 samples collected from two oceanographic cruises in April-May 2001. The occurrence of species in relation to water masses is noted and results are analyzed with regards to the main hydrologic features of the surveyed area. Nineteen species of chaetognaths belonging to 3 genera were identified from the samples. In order of relative abundance, these include: Sagitta enflata, S.bipunctata, S. bedoti, S. neglecta, S. robusta, S. ferox, S. pacifica, S. hexaptera, S. serratodentata, S. decipiens, S. regularis, S. macrocephala, S. minima, S. oceanica, S. pulchra, Pterosagitta draco, Krohnitta subtilis, S. nagae, and S. johorensis. The overall mean density of all arrow worms was 4.85 ind.·m-3 (range 0.90-30.89). Sagitta enflata was the most abundant and frequent species in all stations analyzed and comprised 49.7%. Based on their respective distributions reported in the literature, the results indicate a strong influx of oceanic water from the Pacific Ocean into the Visayan Sea.